Pharmacovigilance - Majagi, Suneel I; Patil, P A (Recent Research in Science and Technology, 2012)
A report on the ‘National Symposium on Pharmacovigilance – 2011’ held at KLE University’s JN Medical College, Belgaum on 12th April 2011